Perbedaan Pengaruh Latihan Chair Dips dan Decline Push-Up Terhadap Kekuatan Otot Lengan Mahasiswa Putra Penkepor UNS - Setyadi, Fantas; Septianingrum, Kartika (Social Science Academic, 2023)
The purpose of this research is to find: ( 1 ) whether there are differences influence of chair dips exercise and decline push-up against the force of the arm muscles on male students of penkepor UNS; ( 2 ) which exercises have the better and effective between chair dips exercise and decline push-up on the muscular strength arm. The kind of research that is used is research experiment. The subject in this research is the male student of penkepor uns which is 56 students. The data which collected in this study in the form of the power of the arm muscles .A test and measurement of who is employed to collect data is by means of a utensil expending a dynamometer. The data technique analysis that used in this research was test a differences ( test – t) with this requirements first like reliability test, test normality, and the homogeneity. After doing the research, the results as follows: ( 1 ) there is a difference in the influence between chair dips exercise and training decline push-up against the force of the arm muscles on male students of penkepor uns the, with Thitung = 6.14 > Ttabel = 1,7033; ( 2 ) the exercise of decline push-up is better on their influence than by the exercise of the chair dips against the force of the arm muscles on male students of penkepor uns the, with an increase in decline push-up = 11,78 % > the exercise of the chair dips = 6,10 %. Based on the results of research can be summed up as follows: ( 1 ) there is a difference in the influence between chair dips exercise and decline push-up against the forces of the arm muscles on male student penkepor uns the; ( 2 ) the exercise of decline push-up is better on influence than the exercise of the chair dips against the forces of the arm muscles on male student penkepor uns the